The cotton buds beach: Marine litter assessment along the Tyrrhenian coast of central Italy following the marine strategy framework directive criteria. Issue 1 (15th December 2016) - Poeta, Gianluca; Battisti, Corrado; Bazzichetto, Manuele; Acosta, Alicia T.R.
Abstract: We assessed the annual accumulation rates of beach litter on the Tyrrhenian coast of central Italy, providing the characterization of litter following European standardized guidelines. Three different sites of a beach were sampled seasonally from spring 2014 to winter 2015. A total of 31, 739 items were removed and classified into 103 categories. Plastic represented the majority (94.4%) of the collected items. We detected temporal and spatial differences in the abundance and composition of litter between seasons and between sites. Furthermore, we found that plastic cotton bud sticks composed > 30% of the total amount of litter and, together with plastic and polystyrene pieces, made up > 70% of the total items. Finally, our results led us to propose that the most effective strategy to reduce litter pollution is to devise specific management procedures focusing on the most abundant items. Highlights: We studied beach litter accumulation rates in central Italy's Tyrrhenian coast. We applied the "Guidance on Monitoring of Marine Litter in European Seas". Cotton bud sticks, plastic and polystyrene pieces were the most abundant items. Seasonal and spatial differences in abundance and composition were identified.